2013
DOI: 10.7314/apjcp.2013.14.6.3503
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Region of p53/Wrap53 Transcripts: Mutational Analysis and Sequence Similarity with microRNA-4732-5p

Abstract: Background: Although the majority of investigations concerned with TP53 and its protein have focused on coding regions, recently a set of studies highlighted significant roles of regulatory elements located in p53 mRNA, especially 5´ UTR. The wrap53α transcript is one of those that acts as a natural antisense agent, forming RNA-RNA hybrids with p53 mRNA and protecting it from degradation. Materials and Methods: In this study, we focused on the mutation status of exon 1α of the WRAP53 gene (according to exon 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The fact that miR‐1246 was reduced after passing through the immunoadsorption column could contribute to this improving in some way, but clinical significance is still unknown. Next, miR‐4732‐5p shares sequence similarity with tumor suppressor gene p53 , and the fact that miR‐4732‐5p was reduced after passing through the immunoadsorption column is worth considering. The sequence of mir‐6088 has been identified, its target and physiological significance is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that miR‐1246 was reduced after passing through the immunoadsorption column could contribute to this improving in some way, but clinical significance is still unknown. Next, miR‐4732‐5p shares sequence similarity with tumor suppressor gene p53 , and the fact that miR‐4732‐5p was reduced after passing through the immunoadsorption column is worth considering. The sequence of mir‐6088 has been identified, its target and physiological significance is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Matsushita et al (44) demonstrated that miR-144-5p targets CCNE1/2 directly to suppress the proliferation of bladder cancer cells. The miR-4732-3p and miR-4732-5p members of the miR-144/451 cluster were identified after the other members, and therefore, few studies currently exist about these miRNAs (45,46). Omura et al (45) suggested that miR-4732-5p may facilitate the prediction of disease recurrence following S-1 chemotherapy treatment through mutational analysis and sequence similarity.…”
Section: Initial Eigenvalue Extracted Eigenvalue --------------------mentioning
confidence: 99%
“…Omura et al (45) suggested that miR-4732-5p may facilitate the prediction of disease recurrence following S-1 chemotherapy treatment through mutational analysis and sequence similarity. Furthermore, Pouladi et al (46) demonstrated that, by binding with the 5'-untranslated region of WRAP53, hsa-miR-4732-5p promoted breast cancer progression. Ultimately, these studies provide evidence demonstrating that members of the miR-144/451 cluster appear to serve important roles in multiple biological pathways, and that individual miRNAs of the miR-144/451 cluster may function as part of different biological pathways in different types of tissues.…”
Section: Initial Eigenvalue Extracted Eigenvalue --------------------mentioning
confidence: 99%
“…tumor could significantly affect the prognosis of patients and response to treatment (Farnebo et al, 2010;Pouladi et al, 2013). Several polymorphisms have been identified in coding and noncoding regions of p53 that some of them have been associated with increased risk of cancer (Whibley et al, 2009).…”
Section: Lack Of Association Ofmentioning
confidence: 99%